Leadership Strategy for Achieving Total Quality Management in a Food and Beverage Company: A Case Study of CV. Berkah Sultan Ali, Sidoarjo - Suhardjo Kristanto; Hesti Ristanto; Venny Resti Fachlovi; Fidyah Arini Kusuma Wardhani (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Fried-chicken fast-food outlets are a promising segment of the food industry because they align closely with the preferences of many Indonesian consumers. Their rapid proliferation has created intense business competition. This study examined the effectiveness of managerial leadership in implementing total quality management (TQM) and its contribution to the success of Ali Chicken, a fried-chicken fast-food brand operated by CV. Berkah Sultan Ali. An empirical descriptive design combining qualitative and quantitative approaches was used. The qualitative analysis employed a radar chart based on gap-analysis data obtained from employee and business-partner assessments. The quantitative analysis used a statistical approach with SPSS version 2.3. Data were collected through individual in-depth interviews with 109 purposively selected respondents comprising management, outlet staff, and loyal customers. The leadership-performance predictors included competence, capability, integrity, intuition, and accountability. All predictor variables had positive values, indicating that the leadership strategy at CV. Berkah Sultan Ali was functioning effectively. The empirical findings also indicated strong customer loyalty, as reflected in regular visits and a monthly customer occupancy rate of at least 87%.